Symbology of Evil in Tolkien’s Middle-earth - Armendáriz Hernández, Joyzukey (2024)
This article explores examples that describe elements in the identification of evil in Middle-earth, found mainly in The Lord of the Rings as well as in some sections of The Silmarillion by the British author J. R. R. Tolkien. Middle-earth as a location, meaning as a cartographic element, becomes a character itself that comprises examples to deepen Tolkien’s conceptualization of evil, mainly in The Two Towers and Mount Doom. Additionally, the evil essence can be perceived more evidently in key characters such as Melkor, Saruman, the Nazgûl, and Denethor, as they develop both hopelessness and a tendency to emptiness, although it also influences Frodo and Sam by allowing in both the eucatastrophic and beneficent resolution of the play. Therefore, the aim is a non-exhaustive approach that proposes a more detailed investigation.